TRADISI HUKUM ADAT BUKA PANTANG MASYARAKAT PULAU ENGGANO DALAM PERSPEKTIF ISLAM - Delta, Yopiko Tri; Dani, Indah Sri Rahma; Anggraini, Devi; Pratama, Zakhi Restu; Ningrum, Sania Dewi Kusuma; Fatmawati, Dea; Nur'aini, Dika; Sihombing, Amrina; Rohan, Sarfraj Yulia; Patria, Muhammad Fajar Tri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Enggano Island is a customary territory (land and sea) for the Enggano customary law community which they call inyah panapue which has been owned from generation to generation based on customary rules and is divided based on sub-tribe territories (kaudar). The traditional law of breaking abstinence on Enggano Island is a universal (entire) custom and is sacred for the Enggano tribal community. Breaking Abstinence during mourning or death is called (yoehore), which is carried out jointly by tribal members. This study aims to conduct research on the customary laws of abstinence from the Enggano Island community from an Islamic perspective. The research method used is a qualitative approach, with data collection techniques in the form of observation, in-depth interviews and secondary data collection, while determining informants is carried out purposively. The tools and materials used in this research are stationery, camera/cellphone, questionnaire data and laptop. If viewed from an Islamic perspective, based on the processes carried out in the Buka Pantang traditional tradition, no elements found that are contrary to Islamic law are found, all processions carried out are based on good intentions shown only by Allah SWT, and solely for the purpose of to honor those who are grieving and pray that the soul of the deceased will be accepted by God in accordance with their beliefs and actions in the world.